Progression of Symptoms and Differences in the Response of Different Skeletal Muscles to the M1592V Mutation of NaV1.4 that Causes Hyperkalemic Periodic Paralysis - Khogali, Shiemaa (Université d'Ottawa / University of Ottawa, 2012)
Hyperkalemic periodic paralysis is characterized by myotonic discharges followed by paralysis. Caused by a mutation in the gene encoding for NaV1.4 channel, patients do not experience symptoms during infancy, but the onset starts between 1-10 years of age. The symptoms severity then increases with age until adolescence. A large increase in gene expression marked by an increase in oxidative capacity of muscles has also been reported in HyperKPP. It is possible that the onset of symptoms is related solely to NaV1.4 channel content/activity reaching a critical level. It is also possible that the onset of some symptoms are due to defective NaV1.4, while other symptoms and the increase in severity with age are related to changes in membrane components as a result of changes in gene expression. To test these possibilities, the progression of paralysis and changes in fiber types were followed with age in HyperKPP mice in relation to changes in NaV1.4 content and activity. Changes in fiber types (index of changes in gene expression), started after the onset of paralysis was observed, which coincided with NaV1.4 channels reaching maximum expression. Therefore, the onset of symptoms was related to defective NaV1.4 channels.
Keywords: Hyperkalemic Periodic Paralysis; Channelopathies; Ion Channels; Sodium Channels; Myosin Fiber types; Muscle physiology; Exercise physiology